Effect of Exercise on Quality of Sleep in Post-Partum Women - Anooshirvan Kazemnejad; Khosro Sadeghniiat Haghighi; Mehrnoosh Amelvalizadeh; Hamid Rajabi; Farzaneh Ashrafinia; Mandana Mirmohammadali (Tehran University of Medical Sciences, 2012)
Background & Aim: Rapid changes experienced after child birth expose mothers to unpleasant experiences such as disturbances in sleep pattern. These experiences threaten health of mothers and infants. Some studies have shown that exercise can be an effective and non-pharmacologic method in improving sleep quality. The purpose of this study was to examine the effect of exercise on sleep quality among postpartum mothers. Methods & Materials: This was a randomized clinical trial. Eighty primiparous women aged 18-35 years were recruited from health centers in Rafsanjan in 2009. The inclusion criteria were singleton pregnancy, lack of any acute and chronic physical and mental illnesses, having healthy and term babies, and having vaginal deliveries. Participants were randomly allocated to the intervention (n=40) and control (n=40) groups. Women in the intervention group received five 30-minutes sessions of Pilates weekly for eight weeks. The PSQI instrument was used to measure the related variables at baseline, forth and eighth weeks after the deliveries. Data were analyzed using the repeated measures ANOVA. Results: Significant improvement was seen in the intervention group within eight weeks follow-up; the interaction within time and group was significant (P=0.02). Comparison of mean sleep quality between the two groups has shown that the intervention was effective (P<0.001). Conclusion: The Pilates exercise was effective in improving quality of sleep in postpartum period.